Solve for x
x = \frac{\sqrt{4814} - 2}{65} \approx 1.036661462
x=\frac{-\sqrt{4814}-2}{65}\approx -1.098199924
Graph
Share
Copied to clipboard
26x^{2}+1.6x=29.6
Use the distributive property to multiply 26x+1.6 by x.
26x^{2}+1.6x-29.6=0
Subtract 29.6 from both sides.
x=\frac{-1.6±\sqrt{1.6^{2}-4\times 26\left(-29.6\right)}}{2\times 26}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 26 for a, 1.6 for b, and -29.6 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-1.6±\sqrt{2.56-4\times 26\left(-29.6\right)}}{2\times 26}
Square 1.6 by squaring both the numerator and the denominator of the fraction.
x=\frac{-1.6±\sqrt{2.56-104\left(-29.6\right)}}{2\times 26}
Multiply -4 times 26.
x=\frac{-1.6±\sqrt{2.56+3078.4}}{2\times 26}
Multiply -104 times -29.6.
x=\frac{-1.6±\sqrt{3080.96}}{2\times 26}
Add 2.56 to 3078.4 by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
x=\frac{-1.6±\frac{4\sqrt{4814}}{5}}{2\times 26}
Take the square root of 3080.96.
x=\frac{-1.6±\frac{4\sqrt{4814}}{5}}{52}
Multiply 2 times 26.
x=\frac{4\sqrt{4814}-8}{5\times 52}
Now solve the equation x=\frac{-1.6±\frac{4\sqrt{4814}}{5}}{52} when ± is plus. Add -1.6 to \frac{4\sqrt{4814}}{5}.
x=\frac{\sqrt{4814}-2}{65}
Divide \frac{-8+4\sqrt{4814}}{5} by 52.
x=\frac{-4\sqrt{4814}-8}{5\times 52}
Now solve the equation x=\frac{-1.6±\frac{4\sqrt{4814}}{5}}{52} when ± is minus. Subtract \frac{4\sqrt{4814}}{5} from -1.6.
x=\frac{-\sqrt{4814}-2}{65}
Divide \frac{-8-4\sqrt{4814}}{5} by 52.
x=\frac{\sqrt{4814}-2}{65} x=\frac{-\sqrt{4814}-2}{65}
The equation is now solved.
26x^{2}+1.6x=29.6
Use the distributive property to multiply 26x+1.6 by x.
\frac{26x^{2}+1.6x}{26}=\frac{29.6}{26}
Divide both sides by 26.
x^{2}+\frac{1.6}{26}x=\frac{29.6}{26}
Dividing by 26 undoes the multiplication by 26.
x^{2}+\frac{4}{65}x=\frac{29.6}{26}
Divide 1.6 by 26.
x^{2}+\frac{4}{65}x=\frac{74}{65}
Divide 29.6 by 26.
x^{2}+\frac{4}{65}x+\frac{2}{65}^{2}=\frac{74}{65}+\frac{2}{65}^{2}
Divide \frac{4}{65}, the coefficient of the x term, by 2 to get \frac{2}{65}. Then add the square of \frac{2}{65} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\frac{4}{65}x+\frac{4}{4225}=\frac{74}{65}+\frac{4}{4225}
Square \frac{2}{65} by squaring both the numerator and the denominator of the fraction.
x^{2}+\frac{4}{65}x+\frac{4}{4225}=\frac{4814}{4225}
Add \frac{74}{65} to \frac{4}{4225} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x+\frac{2}{65}\right)^{2}=\frac{4814}{4225}
Factor x^{2}+\frac{4}{65}x+\frac{4}{4225}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{2}{65}\right)^{2}}=\sqrt{\frac{4814}{4225}}
Take the square root of both sides of the equation.
x+\frac{2}{65}=\frac{\sqrt{4814}}{65} x+\frac{2}{65}=-\frac{\sqrt{4814}}{65}
Simplify.
x=\frac{\sqrt{4814}-2}{65} x=\frac{-\sqrt{4814}-2}{65}
Subtract \frac{2}{65} from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}